Sustainable Bioenergy and Bioproducts Value Added Engineering Applications - Gopalakrishnan, Kasthurirangan; van Leeuwen, J. (Hans); Brown, Robert C. (Green Energy and Technology,, 2012)
Sustainable Bioenergy and Bioproducts considers the recent technological innovations and emerging concepts in biobased energy production and coproducts utilization. Each chapter in  this book has been carefully selected and contributed by experts in the field to provide a good understanding of the various challenges and opportunities associated with sustainable production of biofuel. Sustainable Bioenergy and Bioproducts covers a broad and detailed range of topics including: ·         production capacity of hydrocarbons in the plant kingdom, algae, and microbes; ·         biomass pretreatment for biofuel production; ·         microbial fuel cells; ·         sustainable use of biofuel co-products; ·         bioeconomy and transportation infrastructure impacts and ·         assessment of environmental risks and the life cycle of biofuels. Researchers, practitioners, undergraduate and graduate students engaged in the study of biorenewables, and members of the well-informed public will find Sustainable Bioenergy and Bioproducts  to be a useful and comprehensive research tool, describing the state of the art and recent developments in this field.